Penerapan Model Pembelajaran Auditory Intellectually Repetition Terhadap Kemampuan Pemahaman Konsep Matematika Siswa Kelas X - Arofah, Siti (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2019)
AbstractThe research was a quantitative research with experimental method. The population of research were all tenth grade students of SMAN 1 Wiradesa in the 2018/2019 academic year. The research was conducted to determine the effectiveness of the application of the Auditory Intellectually Repetition (AIR) learning model to the ability to understand mathematical concepts of Grade X students of SMAN 1 Wiradesa. The results showed that the ability to understand mathematical concepts of students in classes taught using the AIR learning model achieved classical completeness, and the average value of the ability to understand mathematical concepts in the experimental class was better than the average value of the conceptual understanding ability in the control class. Based on these two results, it could be concluded that the application of the Auditory Intellectually Repetition learning model was effective on the ability to understand mathematical concepts of Grade X students of SMAN 1 Wiradesa.Â Keywords: AIR, the Ability to Understand Mathematical Concepts